Effective cross hedging: evidence from physical crude palm oil and its non-interrelated energy futures contracts / Ahmad Danial Zainudin, Noryati Ahmad and Fahmi Abdul Rahim - Zainudin, Ahmad Danial; Ahmad, Noryati; Abdul Rahim, Fahmi (Universit Teknologi MARA Cawangan Selangor, 2019)
Recent researchers found that Crude Palm Oil Futures contract (FCPO) in Bursa Malaysia Derivatives is no longer an effective hedging tool to mitigate the price risk in cash market due to the excessive speculation trading activities. This is very alarming to the hedgers hence possible hedge pair alternatives to crude palm oil physical must be identified to ensure that the hedging can be executed effectively. Therefore in this study, Ordinary Least Square, bivariate VAR and bivariate VECM were used to examine whether the non-interrelated energy futures contracts could serve as effective cross-hedging mechanisms for the CPO. Weekly data of agricultural and energy futures contracts from Intercontinental Exchange (ICE), New York Mercantile Exchange (NYMEX), and Tokyo Commodity Exchange (TOCOM) are employed to cross hedge the physical crude palm oil prices. The study starts from 2006 until 2016. Empirical results indicate that bivariate VECM gives more hedging variance reduction. Surprisingly, overall FCPO is still the best futures contract for hedging purposes while Japanese crude oil futures (TOCOM) represents the energy futures market as the best cross hedge alternatives for CPO.